ON THE FORMATION OF THE MANGANESE MAXIMUM IN THE OXYGEN MINIMUM - Johnson K.S.; Coale K.H.; Berelson W.M.; Gordon R.M. (My University, 1996)
A simple model that accounts for the formation of the Mn maximum in the oxygen minimum is presented here. In this model, Mn is proposed to cycle in a constant proportion to carbon, as do nitrogen and phosphorous. Superimposed on the Mn-carbon cycle is the removal of Mn(II) via scavenging onto sinking particles and transport by vertical diffusion. Scavenging is assumed to follow the rate law observed in the laboratory for Mn(II) oxidation. Manganese(II) concentrations were calculated with the model at stations in the Pacific and Atlantic Oceans and compared with measurements of dissolved Mn. All parameters in the model were based on laboratory measurements or field observations. The model reproduced Mn(II) maxima of the correct concentration and at the correct depth. This agreement was observed at a range of oxygen concentrations. The calculations demonstrate that the Mn maximum can form because of a reduction in the pseudo-first order scavenging rate constant (k') within the oxygen minimum. The value of k' will decrease in regions of the water column with low oxygen and pH (k' = k0 [O2] {OH-}2). These regions will accumulate higher dissolved Mn(II) concentrations before the rate of Mn(II) removal, k'[Mn(II)], equals the input from remineralization of POC and a steady state is reached. An additional source of Mn, such as flux from continental margin sediments or dissolution of Mn oxides, is not necessary to account for formation of the Mn maximum.